The effects of drinking water, magnetized through training on some biochemical variables in blood - Jawad, Mohammed (Journal of Physical Education, 2012)
The aim of the study is to identify the effect of drinking magnetic water during the training on some indicators Biochemistry in the blood such as the (Testosterone, H. growth hormone, Total S. protein, S. albumin) were given as the magnetic water for a sample of the Iraqi national team of track and field to the (8) players get magnetic water and compared with a control group from (8) players also they did not get a magnetic water for three months, as it was a test before taking magnetic water, the two groups who training together and then make a test after three months showed the results for the experimental group in the variables (Testosterone, H. growth hormone) and remained within the limits of random variables and for the rest of the study concluded that the magnetic effect of the water and a clear improvement in the viscosity of the blood and the development of some important hormones in the metabolism and construction during the training